2013
DOI: 10.3390/d5020352
|View full text |Cite
|
Sign up to set email alerts
|

Biodiversity Indicators Show Climate Change Will Alter Vegetation in Parks and Protected Areas

Abstract: While multifaceted, a chief aim when designating parks and protected areas is to support the preservation of biological diversity, in part, through representing and conserving the full range of landscape conditions observed throughout a representative area. Parks and protected areas are, however, typically developed using a static interpretation of current biodiversity and landscape conditions. The observed and potential climate change impacts to biodiversity have created a need to also contemplate how parks a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
12
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 67 publications
(92 reference statements)
1
12
0
Order By: Relevance
“…Similar trends have been predicted for other regions of Canada [39]. The amount of change will vary spatially and increase through time with more extreme climate scenarios (Figures 3-5).…”
Section: Discussionsupporting
confidence: 72%
See 2 more Smart Citations
“…Similar trends have been predicted for other regions of Canada [39]. The amount of change will vary spatially and increase through time with more extreme climate scenarios (Figures 3-5).…”
Section: Discussionsupporting
confidence: 72%
“…Though, minimum annual cover model performance was highly variable and as low as 0.1. High variability in predictive success of minimum annual cover may be related to low variance, as minimum annual cover could be low for several different environments [39]. For example, minimum annual cover will be low in deciduous forests as well as grasslands.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a study by Holmes et al (2013), climate data were used to make projections of future vegetation productivity, which can be used as a biodiversity surrogate (see Coops et al 2008). The modeling implemented allowed for pixel-based projections of expected productivity conditions in year 2065 as related to climate projections.…”
Section: Published By Nrc Research Pressmentioning
confidence: 99%
“…The authors found that, given the modeling implemented, the specific characteristics under protection change with climate given the modeling implemented, with implications especially of note for sensitive or specialist species, and over-all conditions are predicted to be more productive and less seasonal. As modeled projections, the maps such as those developed by Holmes et al (2013) are not to be taken as reality (i.e., as an absolute value), but to provide spatial and categorical insight of potential trends to aid in scenario development and planning exercises.…”
Section: Published By Nrc Research Pressmentioning
confidence: 99%